2019
DOI: 10.1155/2019/8086257
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Effect of Alpha-Lipoic Acid in Autoimmune Diseases

Abstract: Αlpha-lipoic acid is a naturally occurring antioxidant in human body and has been widely used as an antioxidant clinically. Accumulating evidences suggested that α-lipoic acid might have immunomodulatory effects on both adaptive and innate immune systems. This review focuses on the evidences and potential targets involved in the immunomodulatory effects of α-lipoic acid. It highlights the fact that α-lipoic acid may have beneficial effects in autoimmune diseases once the immunomodulatory effects can be confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 123 publications
(127 reference statements)
3
17
0
2
Order By: Relevance
“…For the non-exposed infants, we observe a decrease in the abundance of sulfur metabolism and lipoic acid metabolism at 3 and 4-6 months, and of methane metabolism and biotin metabolism at 4-6 months compared to enrollment. These patterns are consistent with previous reports [34,[56][57][58][59][60][61][62]. For example, increased sulfur metabolism is associated with the development of type 1 diabetes [56] and linked to IBD [34].…”
Section: Antibiotic Usesupporting
confidence: 92%
See 1 more Smart Citation
“…For the non-exposed infants, we observe a decrease in the abundance of sulfur metabolism and lipoic acid metabolism at 3 and 4-6 months, and of methane metabolism and biotin metabolism at 4-6 months compared to enrollment. These patterns are consistent with previous reports [34,[56][57][58][59][60][61][62]. For example, increased sulfur metabolism is associated with the development of type 1 diabetes [56] and linked to IBD [34].…”
Section: Antibiotic Usesupporting
confidence: 92%
“…For example, increased sulfur metabolism is associated with the development of type 1 diabetes [56] and linked to IBD [34]. Additionally, lipoic acid is an antioxidant that has been suggested to have beneficial immunomodulatory effects on the innate and adaptive immune systems in autoimmune diseases [57]. Methane has also been shown to have an anti-inflammatory effect, promoting immune tolerance in the intestine when tested in animal models [58,59].…”
Section: Antibiotic Usementioning
confidence: 99%
“…It has been found that with an increasing progression of Alzheimer's disease, GSSG and GSSG/GSH levels also increase. Additionally, a linear correlation between increased GSSG levels and the decreased cognitive status of patients suffering from Alzheimer's disease was observed [8]. Another finding suggests that there may be GSH deficits and abnormalities in the GSH redox cycle in patients with schizophrenia [12].…”
Section: Introductionmentioning
confidence: 91%
“…This compound is able to regulate the immune system in either direct or indirect ways. Studies reviewed in 2019 suggest that LA can be used to treat autoimmune diseases, including systemic lupus erythematosus, rheumatoid arthritis, and primary vasculitis [8]. On top of this, LA reduces the progression of cellular degeneration and improves retinal function [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased sulfur metabolism is associated with the development of T1D [56] and is linked to IBD [34]. Additionally, lipoic acid is an antioxidant that has been suggested to have bene cial immunomodulatory effects on the innate and adaptive immune systems in autoimmune diseases [57]. Methane has also been shown to have an anti-in ammatory effect, promoting immune tolerance in the intestine when tested in animal models [58,59].…”
Section: Mode Of Deliverymentioning
confidence: 99%